FRI0090 SINGLE CENTRE COHORT OF REFRACTORY RHEUMATOID ARTHRITIS ALSO IDENTIFIES A RARE SUBGROUP OF MULTIPLE TARGETED THERAPY CLASS NON-RESPONSE. (June 2019) - Fitton, John; Melville, Andrew; Naraghi, Kamran; Nam, Jacqueline; Dass, Shouvik; Emery, Paul; Buch, Maya
Abstract : Background: Refractory Rheumatoid Arthritis (RefRA) has emerged as an area of unmet need in the biologic era (1). Failure of 3 or more classes of targeted therapy or failure of both an anti-cytokine and a cell-targeted treatment have been proposed as possible definitions (1, 2). The BSRBR-RA reported 6% fulfil RefRA criteria (due to lack of efficacy and/or toxicity; but only including a first line TNF inhibitor bDMARD cohort) (2). Objectives: To evaluate the extent of multi-targeted therapy RefRA in our tertiary RA single-centre experience, and identify any patterns of drug sequencing associated with development of RefRA. Methods: We used a prospective database of RA patients established on targeted therapy, supplemented with information from individual funding requests and a review of our specialised biologic clinic patient notes to identify those who have been prescribed 2 or more classes of targeted therapies. Data on number and type of targeted therapy, and where available, reason for failure has been recorded. Disease activity state and functional outcomes are currently being evaluated Results: Of a cohort of over 1500 RA patients that have received at least 1 targeted therapy, 172 patients have received 3 classes of targeted therapies (reasons for each drug discontinuation has been identified in 166 cases). An additional 50 patients have received multiple (2 or more) TNFi and at least 1 other class of targeted therapy. Table 1 details numbers in each category of RefRA. In those who had failed multiple anti-TNF drugs 39 were switched to a cell-targeted therapy (31 Rituximab, 7 Abatacept), the rest were switched from a TNFi to tocilizumab. 36 out of 39 patients have maintained a response to their cell-targeted therapy after failing multiple anti-cytokines. 5 Patients demonstrate at least 3 primary non-responses with a further 4 further patients with multiple primary non-response and only 1 adverse event. Conclusion: Over 10% of our single-centre targeted therapy exposed cohort demonstrate multi-targeted therapy RefRA. The majority comprise mixed non-response, loss of response and drug toxicity. A rare subgroup of 6% of RefRA demonstrate lack of efficacy to multiple therapies. On-going investigations aim to identify the clinical phenotype, predictors and underlying biology. References: [1] Buch, M.H. Defining refractory rheumatoid arthritis. Ann Rheum Dis. 2018, 77(7), pp.966-969. [2] Kearsley-Fleet, L. et al. Biologic refractory disease in rheumatoid arthritis: results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis. Ann Rheum Dis. 2018, 77(10), pp.1405-1412. Disclosure of Interests: John Fitton: None declared, Andrew Melville: None declared, Kamran Naraghi: None declared, Jacqueline Nam: None declared, Shouvik Dass: None declared, Paul Emery Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, UCB, Roche, Novartis, Gilead, Samsung, Sandoz and Lilly, Maya Buch Grant/research support from: Pfizer LTD, UCB, Consultant for: AbbVie, Eli Lilly, EMD Serono, Pfizer Ltd., Sanofi